Utilization of Oil Palm Fronds Processed By Ammoniation and Fermentation on Dry Material and Organic Material Digestibility in Aceh Cattle. Under supervised - Edi Bigborn Nugraha Capah; Edhy Mirwandhono; Tri Hesti Wahyuni; Hasnudi .; Nevy Diana Hanafi (Jurnal Peternakan Integratif, 2017)
Abstract. The research was conducted at the Laboratory of Animal Biology, Faculty of Agriculture, University of Sumatera Utara in March 2015- June 2015. This study aims to determine the value of dry matter and organic matter processed leaf palm fronds fermentation and ammoniation in cattle Aceh. This study used the Latin Square Design (LSD) 4 x 4. The treatment is Po as the control (untreated), Pf = fermentation (biomol), P2 = ammoniation (urea 3%), P3 = fermentation + ammoniation.The observed variable composed of Consumption and Dry Matter (DMD) and Organic Matter Digestibility (OMD). The result showed that treatments gave not significantly different (P>0.05) on consumption of DM and OM, but gave significantly different effect on DMD and OMD (P<0.05). Average % DMD on treatments Po, PI, P2, P3 : 51.54; 56.65; 51.48; and 63.05 and average % OMD : 58.61; 63.22; 57.28; and 63.05, respectively. The conclusion from this study that utilization of oil palm fronds treated by fermentation or combination between fermentation and ammoniation can increase the dry matter digestibility and organic matter digestibility in Aceh cattle.